LINGUO-SYNERGETIC METHODOLOGY FOR THE RECONSTRUCTION OF THE BRITISH AND UKRAINIAN AXIOCONCEPTOSPHERES - Стефанова, Наталія (Current Issues of Foreign Philology, 2021)
The article critically analyzes the methodological state of linguocultural conceptology and touches upon the problematic issues that require their further development. The main attention is focused on the need to revise the structure of linguistic and cultural concepts and, in this regard, to clarify the terminological designation of these mental formations. It is assumed that each concept of the linguoculture acquires conceptual status only when it is value-evaluative to its members, and therefore a synergetic combination of such entities is axioconceptosphere – motivational continuum of their existence. It is defined that the main task of linguoconceptologists is associated with the search of the relevant for the reconstruction of such motivational continuum of British and Ukrainian ethnic cultures methodological tools, to prove that the allocation of linguistic and cultural concepts of the value layer only as one of the components of their structures simplifies the mental and panchronic (deeply diachronic, etymological, historical and modern) nature of this type of formations. It is proposed three-orthodox (dimensional, cognitive-linguocomparative and linguo-synergetic) methodological approach for the analysis of diachronic and synchronic structure of actually value concepts – TRUTH, GOOD, BEAUTY, BENEFIT that have been identified by ancient thinkers and successive generations of philosophers as the basic value categories and who subsequently laid the foundations of the entire sciences – logic, ethics, aesthetics, which were considered to be a complex system of significant priorities (individual, collective and universal) in the life of each ethnic group and its individual representative. In the article the researcher defined the stages of effective methods and techniques application for the reconstruction in British and Ukrainian axioconceptospheres: the first stage involves the application of methods of cognitive and linguo-comparative studies, in particular, the method of a diachronic review of the etymological versions of the original values of the names of these concepts, their synonyms and derivatives of the etymological sources of the English and Ukrainian languages (with the help of Indo-European etymological dictionaries), the second stage – methods of structural linguistics, modern lexical and cognitive semantics.